PHONOLOGICAL INTERFERENCES IN THE ENGLISH OF BUGINESE STUDENTS - Ani Dyah Astuty (International Journal of Research on English Teaching and Applied Linguistics, 2022)
The problem of phonological interference, which is a key contributor to incorrect pronunciation of English as a foreign language, is still a problem in English language instruction, especially in the area of pronunciation and phonology. Therefore, it's crucial to look into how native language influences how English sounds are produced by EFL students. This study brought to light the phonological errors that Buginese students make when pronouncing English sounds. This study used a qualitative approach, particularly in the form of case studies, to address the objective. 10 second-semester students who are originally from different Buginese regions participated in this research at State University of Makassar. The researcher tested students' pronunciation of English consonants to gather information about the students' phonological interference. The test recording was then translated and examined in light of the students' pronunciation errors. It was discovered that eight consonants were mispronounced by Buginese students, which areconsonants /f/, /v/, /θ/, /z/, /ʃ/, /ʒ/, /dʒ/, and /ð/. Buginese pupils make the closest sounds that are present in Buginese to pronounce these eight consonants. The study's findings were useful in that they helped identify certain English sounds that Buginese pupils had trouble pronouncing, which the English lecturer might use to help the students' pronunciation.